Effect of beetroot juice supplementation on muscle soreness and performance recovery after exercise-induced muscle damage in female volleyball players - Hemmatinafar, M.; Zaremoayedi, L.; Koushkie Jahromi, M.; Alvarez-Alvarado, S.; Wong, A.; Niknam, A.; Suzuki, K.; Imanian, B.; Bagheri, R. (Nutrients, 2023)
Background: Beetroot juice (BRJ) contains various bioactive compounds suggested to be effective in improving athlete recovery. However, the number of studies evaluating the effects of BRJ on recovery and muscle soreness (MS) indicators in female athletes is limited. Therefore, the present study aimed to determine the effects of BRJ consumption on the performance recovery indicators and MS after exercise-induced muscle damage (EIMD) in female volleyball players. Methods: Twelve young female volleyball players were evaluated in this study. We utilized a randomized, cross-over, and double-blind design during two phases with a 30-day interval (wash-out). During each phase, EIMD was performed first, followed by BRJ or placebo (PLA) supplementation for two days (eight servings of 50 mL). Recovery monitoring of performance indicators and MS was performed after EIMD. The results of wall-sit, V sit and reach (VSFT), vertical jump height (VJH), pressure pain threshold (PPT), and thigh swelling (Sw-T) tests were recorded 48 h after EIMD. Also, the Perceived Muscle Soreness was recorded using the visual analog scale (VAS) 12 (MS-12 h), 24 (MS-24 h), and 48 (MS-48 h) hours after EIMD. Results: The data were analyzed using two-way repeated measures of ANOVA at p < 0.05. Compared to PLA, BRJ supplementation improves wall-sit performance after EIMD (p < 0.05), while reducing Sw-T and perceived muscle soreness (p < 0.05). However, no significant difference was observed between PLA and BRJ in VJH and VSFT performance after EIMD (p > 0.05). Conclusions: Our findings indicate that the consumption of BRJ in female volleyball players can be useful for improving some recovery indicators, such as muscle endurance, perceived muscle soreness, and tissue edema, after EIMD.